2018
DOI: 10.1111/jnp.12146
|View full text |Cite
|
Sign up to set email alerts
|

The cognitive profile of Sotos syndrome

Abstract: Sotos syndrome is a congenital overgrowth disorder, associated with intellectual disability. Previous research suggests that Sotos syndrome may be associated with relative strength in verbal ability and relative weakness in non-verbal reasoning ability but this has not been explicitly assessed. To date, the cognitive profile of Sotos syndrome is unknown. Cognitive abilities of a large and representative sample of individuals with Sotos syndrome (N = 52) were assessed using the British Ability Scales (BAS3). Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
27
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(35 citation statements)
references
References 28 publications
6
27
1
1
Order By: Relevance
“…Until recently, the cognitive and behavioural phenotype associated with Sotos syndrome was considerably under-researched and much of the literature was based on small samples (Lane et al 2016 ). However, recent research has investigated the phenotype using larger and more representative samples and this has established that Sotos syndrome is associated with a high prevalence of behavioural symptomatology associated with autism spectrum disorder (ASD), as well as a cognitive profile of relative strength with verbal ability but relative weakness with nonverbal reasoning ability (Lane et al 2017 , 2018 ; Sheth et al 2015 ). The majority of individuals with Sotos syndrome have mild to moderate intellectual disability and in a recent cohort study, the range of reported general conceptual ability (GCA) scores, as assessed by the British Ability Scales 3 (BAS3), was 37–101, with a mean of 60.75 (Lane et al 2018 ).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Until recently, the cognitive and behavioural phenotype associated with Sotos syndrome was considerably under-researched and much of the literature was based on small samples (Lane et al 2016 ). However, recent research has investigated the phenotype using larger and more representative samples and this has established that Sotos syndrome is associated with a high prevalence of behavioural symptomatology associated with autism spectrum disorder (ASD), as well as a cognitive profile of relative strength with verbal ability but relative weakness with nonverbal reasoning ability (Lane et al 2017 , 2018 ; Sheth et al 2015 ). The majority of individuals with Sotos syndrome have mild to moderate intellectual disability and in a recent cohort study, the range of reported general conceptual ability (GCA) scores, as assessed by the British Ability Scales 3 (BAS3), was 37–101, with a mean of 60.75 (Lane et al 2018 ).…”
mentioning
confidence: 99%
“…WS provides a useful comparison for Sotos syndrome for a number of reasons. Specifically, both syndromes are associated with similar overall IQ (mean IQ of approximately 60) and a profile of better verbal ability compared with nonverbal reasoning ability (Lane et al 2018 ; Martens et al 2008 ; Mervis et al 2000 ; Udwin and Yule 1991 ). However, despite better verbal ability compared with nonverbal reasoning ability, WS is associated with delayed and atypical language development (Brock 2007 ).…”
mentioning
confidence: 99%
“…The present study used a relatively small sample, in order to gain a preliminary insight into the ANS and to establish the feasibility of assessing domain-specific numeracy skills within this population, despite intellectual disability and relatively poor numerical reasoning ability (Lane et al 2018). Only one of the Sotos syndrome participants failed to progress to the main dot comparison task, indicating that this task was appropriate for this population.…”
Section: Discussionmentioning
confidence: 99%
“…Recent research has established that Sotos syndrome is associated with an uneven cognitive profile, characterised by relative strength in verbal ability and visuospatial memory but relative weakness in non‐verbal reasoning ability, particularly quantitative reasoning (Lane et al . ). Anecdotal reports of relatively poor numeracy have also been reported (Cole & Hughes ).…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation